Physical activity levels in the university community: A pilot study for the EASIER Project - Guilherme Vilela; Isabel Machado; Alexandre Aleixo; Paulo João; Graça Pinto (Motricidade)
Physical inactivity has been linked to noncommunicable diseases and increasing global mortality rates, highlighting the importance of assessing physical activity levels across different populations (Gilchrist et al., 2020). The aim of this study was to analyse the levels of physical activity in the university community according to gender (female vs. male), educational background (12th year vs. undergraduate vs. master's vs. doctorate) and occupational status (students vs. teachers vs. non-teaching staff), as a pilot study for the EASIER project, which is developing an APP to reduce sedentary behaviour through a combination of exercise and a digital game. A total of 205 participants (112 females and 93 males) were recruited electronically and completed the International Physical Activity Questionnaire Short Form (IPAQ-SF). Physical activity levels were classified into four categories: sedentary, irregularly active, active, and very active. Among the university community, 76% of the participants were classified as sedentary (n=50) or irregularly active (n=106), while only 24% were classified as active (n=33) or very active (n=16). Regarding educational qualifications, 28% of the participants completed high school, 32% had a bachelor's degree, 12% had a master's degree, and 28% had a doctorate. Additionally, 54% of the participants were students, 24% were teachers, and 23% were non-teaching staff. Descriptive statistics and chi-square test were used to compare physical activity levels between sex, educational background, and employment status, with a significance level set at p≤0.05. The results reported mostly sedentary (17% vs 8%) and irregularly active (25% vs 26%) levels of physical activity for female’s vs males, respectively. Regardless of education or employment status, most participants were classified as irregularly active, both representing more than 50% of the total. Furthermore, no significant differences were found in physical activity levels according to gender (p=0.062), education (p=0.167) or employment status (p=0.059). Effective strategies are needed to promote regular physical activity in the university community, regardless of individual characteristics. Awareness and education about the benefits of physical activity, the availability of appropriate infrastructure, programs, and incentive projects for the integration of physical activity in academic routines are some of the advised strategies. In this sense, the EASIER project, which combines physical exercises and a digital game, presents a promising alternative that can improve levels of physical activity and promote a healthy lifestyle in the university community.